From acceptance to rejection: /| Two critical moments of the early history of the Turkish-EEC Relations, 1959 and 1979. - Pekiner, Yeşim. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2004., 2004)
The thesis will focus upon the question that after coming from a long tradition of westernization project, which culminated in Turkey's application to the EEC for associate membership in 1959, why the major political actors chose to freeze Turkey's relations with the EEC in 1978. The thesis focuses upon the anti-westernization sentiments that exacerbated in the late 1970s, as the main reason for the formation of unfavourable policy choices against the EEC. It argues that two major factors were critical in the rise of anti-westernization sentiments, namely, the structural factor and the conjunctural factors. The structural factor is based upon the understanding that the anti-westernization stance was historically embedded in the Turkish society within the framework of centre-periphery polarity that characterizes the Turkish society from the very beginning of the Turkish Republic. It connotes a confrontation between the westernizing central bureaucratic elites and the Eastern-Islamic/peripheral masses. The conjunctural factors is analysed at four levels, namely, the economic factors such as incompatibility of the economic policies of the both parties; foreign policy factors such as the Cyprus Issue and the American Imposed Embargo; political factors, the emergence of multipartyism and the rise of alternative radical minority parties as a result of the neo-legal constitutional framework that was established under the 1961 Constitution. Fourthly ideological-cultural factors, the mobilization of the society along ideological cleavages with the rise of many syndicals, worker's associations, religious organizations, and the nationalist right wing organizations accompanied with their youth organizations and alternative publications.